ANALISIS MINAT BELAJAR SISWA PENGGUNA FACEBOOK DI SMK AL-MUHAJIRIN MENGGALA SEMPURNA TAHUN PELAJARAN 2013/2014 - Arlizon, Raja Arlizon Raja; Asyari, Abu Asyari Abu (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The title of this research is the analysis of student interest in vocational facebook users AL-Muhajirin terms of diligent in learning, Diligent in learning, Neat in doing the task, Having studied schedules, Discipline in the study. The main problem in this research is how the picture of students' interest towards the subjects of facebook users counseling, and student learning outcomes Describing facebook users in the subjects of counseling. The purpose of this study to describe the students' interest towards the subjects of facebook users counseling and to describe the results of student learning in subjects facebook users counseling in class X SMK Al-Muhajirin academic year 2014. The benefit of this research is as inputs to school in order to are use students' interest, as information for further research and as the development of science education in particular. Interest is a mental device that consists of a mixture of feelings, expectations, establishment, prejudice, fear, or other trends that directs a person to a particular choice. (Umaedi, 2002: 8). This research isa descriptivestudyaimed todescribeexactlyhow theresultsofdiligentin learning, Diligentin learning, Neatin doing the task, Havingstudiedschedules, Disciplineinclass X studentof SMKAl-MuhajirinMenggalaCounselingPerfectforlessons. The type of datainthisresearchisprimary dataobtainedthrough questionnairesorquestionnaires. The questionnaireconsistedoffive(5) indicators andeachindicatorhasthirty(30) itemswithtwo optionsnamely"YES andNO". The results obtainedin this studyisthatthe motivationof theteachersofthe socialaspect, andfactorsneedto learnthe toolsofnon-social factorsplay an important rolein generatingstudent interest. Thus it can beina knotout thattheanalysisof sampleswecan knowthe level ofstudent interestin thefacebookuserssmkal-muhajirin, 41.48% werein thehigh category,is 39students, 41.48% are in thecategoryis39students, and17.02% werein thelow categoryis 16studentsfrom94samples. Keywords: Learning Interest